Kenyan counties invest in climate adaptation and peace - Gadeberg, Marianne; Schapendonk, Frans; Medina, Leonardo; Jaskolski, Martina (2025)
Future climate adaptation investments by Kenya’s County Climate Change Fund (CCCF) are poised to promote peace thanks to research-backed recommendations.